Kajian Valuasi Ekonomi Sumberdaya Hutan Mangrove di Desa Bone Pute Kecamatan Tonra Kabupaten Bone - Tang, Beddu; Asmidar, Asmidar; Fikri, Muhammad (JURNAL ILMIAH WAHANA LAUT LESTARI (JIWaLL), 2023)
Bone Regency is geographically located in an area that is influenced by the coast. The coastal resource ecosystem in Bone Regency is dominated by mangrove forests. Mangrove utilization activities that have been carried out so far are physical utilization in the form of continuous use of wood without any replanting activities. The objectives of this study are: 1) To determine the economic value of mangrove forest resources in Bone Pute Village, Tonra District, Bone Regency. 2) To analyze how much the contribution of mangrove forest resources is to the community in the research area of ​​Bone Pute Village, Tonra District, Bone Regency. while the expected benefits of this research are as follows: 1) The results of this study can provide information on the economic value of mangrove forest resources to the community in Bone Pute Village, Tonra District, Bone Regency. 2) For local governments, as input in making policies, planning and managing mangrove forest resources. 3) The knowledge of this research can be used as a reference in the management and development of mangrove ecosystems in other sectors.This research was conducted in the village of Bone Pute, Tonra District, Bone Regency, South Sulawesi Province. The research activity lasted for 6 (six) months, from May to July 2017. From the results of the research it was found that the Total Economic Value of the mangrove ecosystem in Bone Pute Village, Tonra District, Bone Regency with an area of ​​15.20 ha amounted to Rp. 499,469,964, -/year, while the direct benefits of the mangrove ecosystem for the community made the largest contribution, namely Rp. 336,864,000, -/year, indirect benefits of Rp. 128,468,690, existence benefits of Rp. Rp. 31,032,894, while the optional benefits contributed very little, namely Rp. 3,104,220. The potential of mangrove forests in the mangrove forest area of ​​Bone Pute Village, Tonra District, Bone Regency with an area of ​​15.2 ha, and has a contribution to the community in the mangrove forest area of ​​81.13% of the total economic value of mangrove forests / year